STRATEGI PENGEMBANGAN MARKETING MIX DENGAN ANALISIS SWOT PADA GERAI KOPI LIBERIKA DI KABUPATEN TANJUNG JABUNG BARAT - Amalia, Dwi Nurul; Ningsih, Rozaina (Jurnal AGRISEP, 2021)
The productivity of liberica coffee which continues to increase will increase opportunities for the development of liberica coffee agroindustry in Tanjung Jabung Barat Regency. One of the agro-industry efforts to maintain its existence in the business world, namely agro-industry must provide two types of benefits to consumers, namely functional and emotional benefits from products or services. One strategy to improve perceived quality is the application of the marketing mix. This study has the objectives of knowing 1) analyzing the implementation of the marketing mix at Liberika coffee outlets in Tanjung Jabung Barat Regency. 2) identify the marketing mix development strategy at Liberika coffee outlets in Tanjung Jabung Barat Regency. This study uses observation methods and survey methods to the field and see the conditions and potential of Liberika coffee outlets to be input and analysis. The results of research on the application of the marketing mix at Liberika coffee outlets indicate that in general Liberika coffee outlets have implemented a marketing mix strategy well. Liberika coffee outlets have improved perceived quality by implementing a good 7P marketing mix (product, price, place, promotion, human resources, process and physical evidence). The Liberika coffee outlet development strategy is generated through a SWOT analysis. Based on the identification of internal and external factors, the strengths, weaknesses, opportunities and threats can be identified.